A modified T-X family of distributions: classical and Bayesian analysis - Muhammad Aslam; Zahid Asghar; Zawar Hussain; Said Farooq Shah (Journal of Taibah University for Science, 2020)
In this article, we propose a new family of distributions, namely, a modified T-X family of distributions. The case of the newly proposed family is advocated with respect to three most attractive features: flexibility, efficiency and parsimony. The statistical features are established through simulation studies. The applicability of the scheme is further assessed by using two diverse data sets. The performance evaluation study is conducted with respect to five existing distributions while considering various goodness-of-fit criteria. Moreover, the estimation of the parameters is delineated under the classic approach and Bayesian framework. Based on the findings of this research, we see our proposition as a more efficient and parsimonious alternative to the existing well-known cubic transmutation family of distributions. Finally, the flexible nature of the devised family of distributions may project as a useful candidate in survival analysis and reliability theory.